Crystal structure analysis of ebastine [4‐(4‐benzhydryloxy‐1‐piperidyl)‐1‐(4‐tert‐butylphenyl) butan‐1‐one]: an oral histamine antagonist. (1st August 2015) - Sharma, Ranjana; Prasher, Dixit; Tiwari, R. K.
<x xml:space="preserve">Abstract</x> Ebastine belongs to the category of second‐generation non‐sedating H1 receptor antagonists and is chiefly used for the treatment of allergic rhinitis and chronic urticaria. The present paper reports findings on the crystal and molecular structure of ebastine, employing the technique of single‐crystal X‐ray diffraction. Ebastine crystallizes in the monoclinic P21/c space group with unit‐cell dimensions a = 16.5890 (12), b = 10.9575 (8), c = 16.6795 (11) Å, β = 113.623 (2)°, V = 2777.8 (3) Å3, Z = 4 and calculated density amounting to 1.123 Mg m−3. The structure factor value was observed 1016 and final R = 0.0496 for 4360 unique reflections. The piperidine ring in the ebastine molecule was found to exist in a chair conformation, and the C—N bond length was 1.459 (3) Å, thereby showing good agreement with the standard C—N bond length of 1.472 Å.